Intangible Cultural Heritage Safeguarding in Emergencies: The Ukrainian Case - Butsenko, Oleksandr (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
In Ukraine, as elsewhere, war damages or destroys a large part of ICH. The UNESCO documents on Safeguarding Intangible Cultural Heritage in Emergencies highlight the dual role of ICH safeguarding in emergencies, noting that ICH can be vulnerable in difficult times, while it can also help communities to prepare for, respond to, and recover from such threats. The living heritage in Ukraine has become a powerful source of resistance against the aggressors. National identity is based on history, collective memory, knowledge, sense of belonging, and culture. In the Ukrainian case, this foundation has proven to be sustainable and strong, founded on a rich heritage. It is reflected in “resistance identity” which has consolidated Ukrainian society profoundly. Planning post-war development requires us to elaborate clear principles, modalities, and objectives, and convert them into laws, effective institutions, and practices. The war has revealed the role of ICH for the viability of communities and as an essential part of national security.